Analysis of the structural, electronic, elastic and thermodynamic properties of CuAl2X4 (X = O, S) spinel structure. (December 2018) - Obeid, Mohammed M.; Mogulkoc, Y.; Edrees, Shaker J.; Ciftci, Y.O.; Shukur, Majid M.; Al-Marzooqee, M.M. Hussein
Graphical abstract: Energy versus primitive unit cell volume of CuAl2 X4 (X = O, S) spinel structures. Highlights: Fundamental properties of CuAl2 X4 (X = O, S) aluminate spinels have been investigated. The pressure dependence of the elastic constants Cij can be successfully fit by a straight line. CuAl2 X4 (X = O, S) compounds are mechanically stable at ambient conditions. Temperature and pressure dependences of some macroscopic parameters are achieved. Abstract: The structural, electronic, elastic and thermodynamic properties of oxo- and thio-spinels have been predicted based on the ultrasoft pseudo-potential scheme as implemented in the CASTEP code. The exchange-correlation potential was treated within the generalized gradient approximation (GGA-PBE). The calculated structural parameters such as lattice constants and internal parameters are in good agreement with the available experimental data. The ground state electronic band structure revealed that CuAl2 X4 (XO, S) spinels are direct band gap semiconductors with a transition along Г-Г symmetry points. The calculated values of elastic constants satisfy the Born criteria at ambient conditions and confirm that the spinel structures of CuAl2 O4 and CuAl2 S4 are mechanically stable. The thiospinel structure may have a phase transition under pressure, due to the negative value of C 44 . The influence of temperature and pressure on macroscopic characteristics of CuAl2 O4 and CuAl2 S4 compounds was estimated using the quasi-harmonic Debye model.